2021
DOI: 10.1016/j.ijid.2021.08.027
|View full text |Cite
|
Sign up to set email alerts
|

External Validation and Recalibration of the CURB-65 and PSI for Predicting 30-Day Mortality and Critical Care Intervention in Multiethnic Patients with COVID-19

Abstract: Objectives To validate and recalibrate the CURB-65 and pneumonia severity index (PSI) in predicting 30-day mortality and critical care intervention (CCI) in a multiethnic population with COVID-19, along with evaluating both models in predicting CCI. Methods Retrospective data was collected for 1181 patients admitted to the largest hospital in Qatar with COVID-19 pneumonia. The area under the curve (AUC), calibration curves, and other metrics were bootstrapped to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“… [33] Lastly, in a cohort of 1181 patients from Qatar, a C-statistic of 0.78 (95% CI 0.70-0.86) was reported. [34] Overall, the discriminative performance of the CURB-65 reported by these studies varied from moderate to good. Similar to our study, none of the aforementioned studies assessed model calibration of the CURB-65 score.…”
Section: Discussionmentioning
confidence: 89%
“… [33] Lastly, in a cohort of 1181 patients from Qatar, a C-statistic of 0.78 (95% CI 0.70-0.86) was reported. [34] Overall, the discriminative performance of the CURB-65 reported by these studies varied from moderate to good. Similar to our study, none of the aforementioned studies assessed model calibration of the CURB-65 score.…”
Section: Discussionmentioning
confidence: 89%
“…Aging, male sex, cardiovascular risk factors and cardiovascular disease, kidney and lung dysfunction, cancer and autoimmune diseases have been associated with worse clinical outcomes among patients with COVID-19 [ 2 , 5 , 23 ]. In the presence of comorbidities, the classic pneumonia scores such as CURB-65 and PSI [ 24 , 25 ] as well as a quicker clinical score, namely qSOFA [ 26 , 27 ], have shown a good correlation with poor prognosis. However, so far no study has investigated a cohort free of comorbidities and stable admission criteria, homogeneous and stable therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Elmoheen et al reported that CURB-65 outperformed pneumonia severity index in predicting 30-day mortality and critical care intervention in a multiethnic population from Qatar (2021). 31 Besides the CURB-65 score, it could be studied if including procalcitonin, D-dimer, and ferritin could help predict sepsis's inflammatory and coagulation states. Additionally, other scores, such as sequential organ failure assessment (SOFA), could be used for further evaluation of patients in the intensive care setting.…”
Section: Discussionmentioning
confidence: 99%